Diesel Engine Control And In-Cylinder Peak Pressure Monitoring System Using Raspberry PI - Yeo, Ying Heng (Universiti Sains Malaysia, 2019)
Diesel engine is one of the internal combustion engines (ICE) which provides a higher efficiency compare to gasoline engine. However, the cycle to cycle variation of diesel engine causes a decrease in efficiency and increase in pollutant emission. To solve the problem, different methods have been investigated by the researches over the past decades. In this project, an engine control unit (ECU) of diesel engine has been developed using Raspberry Pi 3 B. The ECU has the capability to perform calculation which requires considerable computational power. It has the function of real time injection timing alteration based on the calculation it performs on sensors data. A simple closed loop algorithm is developed to control the start of injection timing (SOI) of a single cylinder diesel engine using the ECU. The main purpose of the closed loop system is to evaluate the capability of ECU in executing the closed loop algorithm within the time span of less than one combustion cycle. It is found that the ECU developed is able to execute the closed loop system without failure. The mean peak pressure can be maintained at a value close to the setpoint. The closed loop algorithm can be performed in the time span of less than one combustion cycle. The only drawback is that the cycle to cycle reduction ability of closed loop system is not effective enough. The standard deviation of peak pressure increases as the closed loop system is activated when the change in SOI during each combustion cycle is larger than 0.5 ° after top dead center (ATDC)